Justice and the City: A Reading of Amos 3:9-15 - Ben-Dov, Yonatan (Vetus Testamentum, 2017)
The article strives to understand the urban prophecies in the Book of Amos with a view to spatial and literary concepts. Amos 3:9-15 is a collection of short prophecies, with v. 12 serving as its linchpin. The imagery of vv. 9-11 is part of an urban tradition in biblical literature, which underscores the importance of justice and peace for the maintenance of the city. Verses 12 and 15 constitute one prophecy about Samaria, which intensifies the tension between the city and its surroundings by contrasting items from the urban scenery with a gruesome picture of the lion in prey. Vv. 13-14 constitute a Bethel prophecy, introduced in between the Samaria prophecies. The city is poetically defined by the unification of its surroundings (the wall) with the edifices at its heart. Several cruxes in the interpretation of Amos 3:9-15 are elucidated throughout the discussion.